Does non-operative management of iatrogenic bile duct injury result in impaired quality of life? A systematic review. Issue 2 (April 2020) - Halle-Smith, James M.; Hodson, James; Stevens, Lewis; Mirza, Darius F.; Roberts, Keith J.
Abstract: Background: Several studies have reported the effect of bile duct injury (BDI) on health-related quality of life (HRQOL) with conflicting results. This systematic review aims to study the impact of patient and treatment factors on HRQOL after BDI. Methods: A search of the PubMed database was performed and studies were reviewed as per the PRISMA guidelines. Selected studies (n = 11) were then divided into two subgroups depending on whether they found HRQOL to be similar or worse between BDI and control groups. Pooled rates of surgical repair and major BDI were calculated for each of these subgroups. Results: Surgical repair rates were 99% (95% CI: 96%–99%) in studies where the BDI patients had similar outcomes to controls, compared to 78% (40%–100%) where their outcomes were significantly worse (p = 0.091). The major BDI rate was 51% (95% CI: 42%–61%) in studies where the BDI patients had similar outcomes to controls, compared to 72% (41%–94%) where their outcomes were significantly worse (p = 0.322). Considerable heterogeneity was present within the two subgroups (I 2 : 68–99%). Discussion: HRQOL may be adversely affected amongst patients with BDI who do not undergo surgical repair. Significant heterogeneity of data suggests the need for standardised HRQOL tools and injury severity systems when assessing outcomes after BDI. Highlights: Surgical repair of bile duct injury is related to improved health-related quality of life (HRQOL). HRQOL is adversely affected amongst patients with a major bile duct injury. There is significant heterogeneity in the reporting of HRQOL after bile duct injury. Standardised and disease specific tools should be used to improve the quality of data reported in this field.